Mineralogy and Surface Charge Properties of two Acid Sulfate Soils from Peninsular Malaysia - Jusop, Shamsuddin; Paramananthan, S.; Nik Wan, Nik Mokhtar (1986)
Two acid sulfate soils sampled from an oil palm estate in Perak, Peninsular Malaysia, were studied. The soils were characterized by a low pH and the presence of yellowish mottles, which were identified as jarosite and/or natrojarosite. Other minerals present were kaolinite, mica, mica-smectite and smectite. The negative charges on the soil surface were found to increase significantly with an increase in pH. This increase was not related to the presence of oxides and/or hydroxides as these materials were present in very small amounts in the soils. On account of the increase in the negative charges with an increase in pH, it is suggested that CEC of acid sulfate soils be determined at soil pH to give a better reflection of the soil properties. Further, it was found that the soils were highly buffered at pH 3 - 5. The strong buffering at this pH range was related to the presence of high amounts ofaluminium in the soil.